Estimating seed dispersal distance: A comparison of methods using animal movement and plant genetic data on two primate‐dispersed Neotropical plant species - Tiziana A. Gelmi‐Candusso; Ronald Bialozyt; Darja Slana; Ricardo Zárate Gómez; Eckhard W. Heymann; Katrin Heer (Ecology and Evolution, 2019)
Abstract Seed dispersal distance (SDD) critically influences the survival of seedlings, spatial patterns of genetic diversity within plant populations, and gene flow among plant populations. In animal‐dispersed species, foraging behavior and movement patterns determine SDD. Direct observations of seed dispersal events by animals in natural plant populations are mostly constrained by the high mobility and low visibility of seed dispersers. Therefore, diverse alternative methods are used to estimate seed dispersal distance, but direct comparisons of these approaches within the same seed dispersal system are mostly missing. We investigated two plant species with different life history traits, Leonia cymosa and Parkia panurensis, exclusively dispersed by two tamarin species, Saguinus mystax and Leontocebus nigrifrons. We compared SDD estimates obtained from direct observations, genetic identification of mother plants from seed coats, parentage analysis of seedlings/saplings, and phenomenological and mechanistic modeling approaches. SDD derived from the different methods ranged between 158 and 201 m for P. panurensis and between 178 and 318 m for L. cymosa. In P. panurensis, the modeling approaches resulted in moderately higher estimates than observations and genotyping of seed coats. In L. cymosa, parentage analysis resulted in a lower estimate than all other methods. Overall, SDD estimates for P. panurensis (179 ± 16 m; mean ± SD) were significantly lower than for L. cymosa (266 ± 59 m; mean ± SD). Differences among methods were related to processes of the seed dispersal loop integrated by the respective methods (e.g., seed deposition or seedling distribution). We discuss the merits and limitations of each method and highlight the aspects to be considered when comparing SDD derived from different methodologies. Differences among plant species were related to differences in reproductive traits influencing gut passage time and feeding behavior, highlighting the importance of plant traits on animal‐mediated seed dispersal distance.